Regulasi Pengakuan Hukum Negara Atas Tanah Yang Dikuasai/Dimiliki Oleh Masyarakat Hukum Adat: Relevan Bagi Papua - Tristam Pascal Moeliono (Jurnal Administrasi Publik, 2014)
The main purpose of this paper is to explain the particular arrangements and state recognition of customary rights (indigenous peoples' management control righst of the land where they live) in Indonesia. Two issues are addressed, firstly, whether the state recognition of the existence of customary law community is constitutive or merely declarative. Secondly, whether the scope of the recognition of the state covers just about the land or it also includes the natural resources attached to it. To address the above issues, this article explores the right of state to control customary rights on land as mandated in State Constitution 1945 and Basic Agrarian Law No.5/1960. In addition it also describes of how this concept of customary right on land lays foundations for managing natural resources such as gas and oil, forestry, as well as mining. It also connects to the long term goals of the state as mentioned in Law No.17/2007 regarding Long Term National Development Plan 2005-2025 and Law No.26/2007 regarding spatial arrangement plan (Rencana Tata Ruang). Those laws than finally is connected to Law No.2/2012 and Government Regulation No.71/2012 regarding the land acquisition for development activities and public interest, as well as land acquisition for private sector activities in the context of both domestic and foreign investment. Two conclusions are made, firstly, mimicking and imposing of legal system and development ideology from the parent state (NKRI) should be avoided. The challenge is how to bring the state (government of Papua) in charge and how to maintain the legitimacy of the presence of urbanized modern society (urban) in front of indigenous peoples. Secondly, the main problem is not how to develop regulation framework for better recognition of the customary law, but how modern capitalist economy should not harmful to the existing traditional community life.